Empires of the Sea Maritime Power Networks in World History - Strootman, Rolf; van den Eijnde, Floris; van Wijk, Roy (Cultural Interactions in the Mediterranean, 2019)
Empires of the Sea brings together studies of maritime empires from the Bronze Age to the Eighteenth Century. The volume develops the category of maritime empire as a specific type of empire in both European and 'non-western' history.; Readership: Anyone concerned with World History, and specifically those interested in maritime history and the comparative study of empires.